An Implementation of A* Algorithm to Tourism Destination - Annisa Afida; Muhammad Akid Musyafa; Elvanisa Ayu Muhsina; Bambang Sugiantoro (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2015)
The tourist sector contributes significantly to the country’s development and has a big potential capital. Therefore, it could as well contribute to innovations of communication and information technology. Development of the tourism sector should be based on technology development. The district of Bantul has a big variety of several important and tourism sights, which are spread all over the District with a wide range of different routes and locations. Therefore, it might be confusing for tourist to locate them. Based on this problem, the writer creates an information system which can be integrated in Google Maps as a visual media map including all sight-seeing spots completed with an application which efficiently recommends the shortest route using A* algorithm. From the result of the research conducted, the result of the browsing system is compared to manual calculation giving the same results.